BENTUK PELANGGARAN KODE ETIK SERTA SANKSI PELANGGARAN KODE ETIK PROFESI HAKIM TINDAK PIDANA KORUPSI - Sandi, Aprila; Wijayanti, Ajeng; Imania Arafah, Ghina Hani; Kaffah Milati, Silma; Bifadillah, Putranto (Moderation | Journal of Islamic Studies Review, 2022)
The purpose of this study is to find out the forms of violations of the professional code of ethics of judges for corruption and to find out what sanctions are given to judges who violate the judge's professional code of ethics. The research method used in this research is the type of normative research where the data source is obtained by literature study and the analysis method uses qualitative research which is analyzed descriptively. The professionalism of a judge is not only because he is capable, intellectual, and successful in his field as a judge, but the behavioral aspect is also part of the assessment that must be possessed in implementing the Code of Ethics of Judges or Professional Ethics of Judges to uphold law and justice. The importance of professional ethics for judges in law enforcement should be a guideline for judges in carrying out their professional duties who are pious to God Almighty, fair, wise/authoritative, virtuous, and honest.